2018
DOI: 10.19080/gjorm.2018.06.555678
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Postnatal Care Service Utilization and Associated Factors in Asella Town, Arsi Zone, Oromiya Regional State, Ethiopia

Abstract: Post-natal care refers to the assistance given to the mothers and the babies for a period of six weeks from the time of delivery. It is believed to be low in Ethiopia. This study provided postnatal care service utilization information in the study area.Objectives: To assess postnatal care service utilization prevalence in Asella Town,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
1
4
2
Order By: Relevance
“…This study revealed that 23.3% (95% CI 18.9% to 27.9%) of women received EPNC. This result is lower than the study reported in some African countries such as Myanmar (72.1%), 26 Zambia (63%), 27 Builsa district (62%), 28 Hadiya zone (51.4%), 29 Uganda (50%), 7 Assela town (37.5%), 30 Adigrat town (34.3%) 11 and Debremarkos town (33.5%). 31 However, it is higher than the findings of studies conducted in China (17%), 32 Tanzania (10.4%), 33 South Sudan (11.4%)and 8 Debremarkos town in Ethiopia (16.2%).…”
Section: Discussioncontrasting
confidence: 59%
“…This study revealed that 23.3% (95% CI 18.9% to 27.9%) of women received EPNC. This result is lower than the study reported in some African countries such as Myanmar (72.1%), 26 Zambia (63%), 27 Builsa district (62%), 28 Hadiya zone (51.4%), 29 Uganda (50%), 7 Assela town (37.5%), 30 Adigrat town (34.3%) 11 and Debremarkos town (33.5%). 31 However, it is higher than the findings of studies conducted in China (17%), 32 Tanzania (10.4%), 33 South Sudan (11.4%)and 8 Debremarkos town in Ethiopia (16.2%).…”
Section: Discussioncontrasting
confidence: 59%
“…For uncomplicated vaginal delivery in the health facility, a mother discharged before 24 hours is considered as non-utilizer unless she gets an additional visit within 42 days of delivery [19,20]. Controls were women who utilized postnatal services, which was measured if the mothers received one of the postnatal services; immunization, family planning and health education on childcare, breastfeeding, physiotherapy, physical examination, treatment, and counseling service [10,21].…”
Section: Variables and Measurementsmentioning
confidence: 99%
“…An interviewer-administered standardized structured questionnaire was developed and used after reviewing other similar studies [6,10,[29][30][31][32][33][34]. The questionnaire has consisted of a range of variables; sociodemographic and cultural, socio-economic, and knowledge, attitudes, and health system-related characteristics.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations